Evidence-based policy responses to strengthen health, community and legislative systems that care for women in Australia with female genital mutilation / cutting - Nesrin Varol; John J. Hall; Kirsten Black; Sabera Turkmani; Angela Dawson (BMC, 2017)
Abstract Background The physical and psychological impact of female genital mutilation / cutting (FGM/C) can be substantial, long term, and irreversible. Parts of the health sector in Australia have developed guidelines in the management of FGM/C, but large gaps exist in community and professional knowledge of the consequences and treatment of FGM/C. The prevalence of FGM/C amongst Australian women is unknown. Our article reviews the literature on research on FGM/C in Australia, which focuses on health system response to women and girls with FGM/C. Recommendations are made for policy reform in health, legislation, and community programs to provide the best healthcare, protect children, and help communities abandon this harmful practice. Main body Midwives and doctors in Australia acknowledged a lack of knowledge on FGM/C, clinical guidelines and consequences for maternity care. In a metropolitan Australian hospital with specialised FGM/C care, women with FGM/C had similar obstetric outcomes as women without FGM/C, underlining the importance of holistic FGM/C clinics. Greater focus on integration of refugee and migrant populations into their new cultures may be an important way of facilitating the abandonment of this practice, as is education of communities that practise FGM/C, and experts involved in the care and protection of children. Men could be important advocates for protecting women and girls from violence and FGM/C through a man-to-man strategy with programs focussing on men's health and other personal issues, education, and communication. The Australian Government has identified gender-based violence as an area of priority and has been implementing a National plan to reduce violence against women and their children 2010-2022. A multidisciplinary network of experts on FGM/C could be established within this taskforce to develop well-defined and rapid referral pathways to care for and protect these children, as well as coordinate education and prevention programs to help communities abandon this harmful practice. Conclusion Countries of migration can be part of the solution for abandonment of FGM/C through community interventions and implementation of national and coordinated training in FGM/C of experts involved in the care and protection of children and women. The global focus on collaboration on research, training and prevention programs should be fostered between countries of FGM/C prevalence and migration.